Antioxidant activity of estrogens - Stachowiak, Grzegorz; Połać, Ireneusz; Jędrzejczyk, Sławomir; Pertyński, Tomasz; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2003)
The activity of reactive oxygen intermediates (free radicals) is one of the mechanisms of the ageing process. In particular, lipid peroxidation is the main factor of cells ageing and makes lipoproteins more atherogenic. There are still many studies on prophylactic administration of antioxidant substances as a diet or drugs. At present more and more attention is paid to the antioxidant effect of estrogens, administered as part of hormonal replacement therapy in peri- and postmenopausal women.